USE OF MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHING INFORMATICS - Mukhabbat Xudoynazarovna Xalmetova (Journal Park Publishing, 2023)
This article discusses the model of interdisciplinary communication and the use of innovative technologies in the teaching of computer science in higher education and the use of the laws of interdisciplinary communication.
Keywords: Practical activity, pedagogical skills, mental activity, physical activity, computer technology.